Twenty years of surveillance of Invasive Meningococcal Diseases in Puglia, Italy - Paola Stefanelli; Cecilia Fazio; Arianna Neri; Anna Di Taranto; Maria Labonia; Anna Lisa De Robertis; Daniela Loconsole; Domenico Martinelli; Maria Chironna (Istituto Superiore di Sanità, 2015)
INTRODUCTION: The study aims to investigate the change in the burden of disease and the microbiological characteristics of Invasive Meningococcal Disease (IMD) in Puglia in comparison with overall incidence from 1994 through 2014. METHODS: Data are gathered in the frame of the National Surveillance System coordinated by the National Reference Laboratory (NRL) of the Istituto Superiore di Sanit`. RESULTS: In Puglia, from 1994 through 2014, the average incidence of IMD was 0.2 per 100 000 inhabitants, below the national average value (0.33). IMD cases tended to be older than the other cases reported in Italy (median age 19 vs 16). The case-fatality rate was 20.4% in Puglia vs 13.3% in Italy. Serogroups B and C were most frequently identified. Serogroups C and Y presented a fairly clonal pattern, whereas serogroup B was genetically rather heterogeneous. CONCLUSION: Surveillance systems are critical in monitoring any change in the epidemiology of IMD.